THE TITLE WRITTEN USING UPPERCASE FORMAT ANALYSIS OF FACTORS INFLUENCING STUDENTS' INTEREST IN INVESTING IN THE CAPITAL MARKET (Case Study on University of Semarang Students) - Citra Andriani Kusumawati; Fredericho Mego Sundoro; Adhi Widyakto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to find out and test the influence of investment knowledge, Income, Return, Risk, Minimal Capital on students' investment interests. The type and source of data in this study is to use primary data. The sample in this study was a part of the population of 86 active employee class students in the even semester of 2021/2022, Faculty of Economics, University of Semarang. The results of hypothesis testing show the existence of Investment Knowledge positively and significantly to Investment Interest. Income has a positive and significant effect on Investment Interest, Investment Return has a positive and significant effect on Investment Interest, Risk has a positive and significant effect on Investment Interest. And Investment Capital has a positive and insignificant effect on Investment Interest